New Formulation of the Law of Universal Gravitation - Obara, Robert (Annals of Mathematics and Physics, 2025)
New relationships for the force of gravity, gravitational acceleration, gravitational potential and escape velocity have been formulated. It has been shown that these quantities are dependent on the difference of relativistic gravitational coefficient measured at the ends of the Compton wave for a body placed in a gravitational field. The dependence force of gravity on the Compton period is presented. Formulas of force of gravity are presented in both relativistic and nonrelativistic form.